Архитектоника субстантивных терминов подъязыка сельскохозяйственной и почвенной микробиологии - Кислухина, М.В. (Культура народов Причерноморья, 2003)
In this paper we describe the structural peculiarities of the terms of agricultural and soil microbiology. Also we present different definitions of the term and сharacteristic features of scientific style.